Drowning - David B. Richards (African Journal of Emergency Medicine, 2011)
Drowning is responsible for significant preventable morbidity and mortality worldwide causing more deaths than war. Over the past 10 years our understanding of the causative factors, pathophysiology, management, outcomes, and even the terminology used has changed. Aggressive pulmonary support has proven to be essential to optimizing the victim’s chances for a favorable outcome. Hypoventilation, steroids, dehydration, barbiturate coma, and neuromuscular blockade have not been shown to affect outcomes as previously thought. Further, no prognostic scale or clinical presentation has been found which accurately predicts long-term neurologic outcome. Simple preventative measures and educational efforts can be effective in preventing a major cause of morbidity and mortality in often young and healthy members of society.